The Effect of Return On Assets (ROA) and Dividend Payout Ratio (DPR) on Return of LQ45 Company Shares Listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 Period - Anggia Yustiana Fahira; Dudi Haryadi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
The purpose of this research is to analyze the influence of return on assets and dividend payout ratio on stock return. Their search population are companies incorporated in LQ45 index and listed on the Indonesia Stock Exchange year 2019-2021. By using purposive sampling method, obtained 63 financial statements from 21 different companies that meet predetermined criteria. The research conducted using multiple regression analysis method. The result showed that return on assets has no significant effect on stock return, dividend payout ratio negatively and significantly affected stock return, also simultaneously return on assets and dividend payout ratio have no significant effect on stock return.